The Importance of the Binding of Factor Xa to Phospholipids in the Inhibitory Mechanism of Tissue Factor Pathway Inhibitor: The Transmembrane and Cytoplasmic Domains of Tissue Factor Are not Essential for the Inhibitory Action of Tissue Factor Pathway Inhibitor - Kazama, Yoshiaki (Thrombosis and Haemostasis, 1997)
To investigate the inhibitory mechanism of tissue factor pathway inhibitor (TFPI), an attempt was made to examine the inhibitory activity of TFPI toward the factor Vila-truncated tissue factor (TF1-219) complex, which lacks its transmembrane and cytoplasmic domains. Factor VIIa-TF1-219 activity was significantly inhibited by TFPI-factor Xa complex in the presence of phospholipids, but was not in the absence of phospholipids. In addition, TFPI did not inhibit factor VIIa-TF1-219activity in the presence of γ-carboxyglutamic acid-domainless factor Xa. The ability of TFPI-factor Xa complex to inhibit factor VIIa-TF1-219 activity was totally dependent on the presence of phospholipids and was neutralized by prothrombin fragment 1 in a dose-dependent manner. These results indicate that the transmembrane and cytoplasmic domains of tissue factor are not essential for the inhibitory mechanism of TFPI and confirm that the binding of factor Xa to phospholipids through its γ-carboxyglutamic acid domain is essential for this reaction.